8a-(a-4)=

Simple and best practice solution for 8a-(a-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8a-(a-4)= equation:


Simplifying
8a + -1(a + -4) = 0

Reorder the terms:
8a + -1(-4 + a) = 0
8a + (-4 * -1 + a * -1) = 0
8a + (4 + -1a) = 0

Reorder the terms:
4 + 8a + -1a = 0

Combine like terms: 8a + -1a = 7a
4 + 7a = 0

Solving
4 + 7a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 7a = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 7a = 0 + -4
7a = 0 + -4

Combine like terms: 0 + -4 = -4
7a = -4

Divide each side by '7'.
a = -0.5714285714

Simplifying
a = -0.5714285714

See similar equations:

| 2h-8=10-4h | | 7y-3=3y+25 | | 42+5=71 | | 2ba+3ab= | | 1/2X1/2=2/5 | | logx(20)=3 | | 3y-11=21 | | 3x+m=16 | | -2.8/7 | | factorisemn=m | | 3(2x-1)=x+27 | | 15-4(2a-1)= | | 3(x-4)=24 | | 4cosx+1=0 | | y=9x^3-7x+2 | | 4c-1=-5 | | 12t=howmenylb | | X+7.1=4.1 | | 3p^2-6p=1 | | 187=88-y | | 1+(4*4)-2= | | S+4.1=8.1 | | 1*10= | | n^2/3-n/6 | | 52x+3=1 | | (3/4)n | | y^2/2=32 | | 9a-8+6a-4= | | 2(3-8)+7= | | y=-5+4sinx | | (5)+(-14)= | | f(x)=-0.91666667*x+1.5 |

Equations solver categories